Sinonasal or nasopharyngeal undifferentiated Carcinoma?: diagnostic pitfall and the role of Epstein-Barrvirus (EBV) and human papillomavirus(HPV) examination - Wahyu Tri Widayati; Ery Kus Dwianingsih; Bustanul Ardianto; Didik Setyo Heriyanto; Sagung Rai Indrasari; Camelia Herdini; . Irianiwati (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Undifferentiated carcinoma of the head and neck is frequently observed in nasopharynx, however it may also occur in oropharynx, salivary gland and sinonasal. Overlapping lesions in those regionscreate difficulty in determining the origin of the tumor. Thus, it causes diagnostic pitfall not only for pathologists, but also for clinicians. A 40 yearold man, presented with nasal obstruction, epistaxis, diplopia, and headache for a yearand showed nasal cavitysinistra and nasopharynx masses on CT-scan. Lymph node enlargement was not detected. First biopsywas performed and histopathologically diagnosed as nasopharyngeal undifferentiated carcinoma(NPC), extended into nasal cavity. Chemo-radiation protocol for NPC was conducted, and showing uncomplete response. Second biopsy was done, and reviewed with the first biopsy result. Thetumourwas arranged insolid, syncytial and trabecular pattern, with vesicular nuclei, prominent nucleoli, and lack of lymphoplasmacytic infiltrat. Immunohistochemistry (IHC) analysis of p16, EBNA1 and LMP1 were negative. PCR analysis of HPV-18 was positive, while EBV detection showed negative result. General association of EBV with NPC suggests that the presence of latent EBV infection can serve as a positive marker for NPC. Therefore, in this case, the EBV negativity and strong HPV association led to diagnosis of SNUC. The distinction of sinonasal undifferentiated carcinoma (SNUC) or from NPC was important for appropriate management and therapy.